Chaotic dynamics of a double-well Bose-Einstein condensate. - Rajagopal, Kalai Kumar; Cheng, LongJun (Communications in Physics, 2023)
We study the dynamics of a double-well BEC system subjected to oscillating dissipation. The macroscopic model is described within the mean-field approximation while noise effect due large reservoir fluctuation has been averaged out to zero. We chose a simple dissipative memory kernel to produce a time-dependant oscillating dissipation. Our numerically calculated phase-space and Lyapunov exponents shows enhances route to chaos as one increases driven dissipations amplitude.